If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(4x-3)-60=30
We move all terms to the left:
3(4x-3)-60-(30)=0
We add all the numbers together, and all the variables
3(4x-3)-90=0
We multiply parentheses
12x-9-90=0
We add all the numbers together, and all the variables
12x-99=0
We move all terms containing x to the left, all other terms to the right
12x=99
x=99/12
x=8+1/4
| 14/y+4/y=3 | | 17*t+22*(4-t)=70 | | 9x-(7x+3)=5x-15 | | 12(×+5)=4x | | X/3x+5=50 | | 13u+12=9u+16 | | −6+3x=−48 | | d^2=2-22 | | N²+11n=522 | | 4.5*2.24*9.9=x | | 5x+4x=6400 | | Y=1/3x-20/9 | | 6(x-5)+10=2(3x-4) | | -15x+175=15x+20 | | Y=3x+20/3 | | f(-4)=4(-4)+6 | | 5x+1/2=x-1/2 | | 8-)8x+9)=0 | | (8.z)÷7=0.8 | | 47=11+6y | | 2v+5=14 | | 8+(x÷2)=-12 | | 8×(x/2)=-12 | | -(-9x)=x | | (-78)x=92 | | 4m3+16m=3m2–m | | (a÷6)-1=0.4 | | 6m+12=35 | | 9j-6+j=3(5j-2) | | w/7=31 | | w÷7=31 | | 4x+24=-30+5x |